Musculoskeletal Disorders among Faculty Members and Impact of Work-Related Factors on Its Prevalen - Mozhgan Modarresi; Ali Mohammad Fallah Tafti; Mohammad Karim Touri; Arezoo Aghakoochak (Golestan University Of Medical Sciences, 2017)
Introduction: Nowadays, musculoskeletal disorders (MSDs) are one of the most common work-related problems in the world. The aim of this present study was to determine the prevalence of MSDs and their relationship with work-related factors among tutors working at Shahid Sadoughi University of Medical Sciences in Yazd, Iran. Materials and Methods: This cross sectional study was conducted on 113 tutors at the Shahid Sadoughi University of Medical Sciences in 2015. Data were collected by a standard self-administered questionnaire consisting of three major parts: a) demographic and work-related variables, b) musculoskeletal symptoms, c) a modified version of the Standard Nordic Questionnaire. The data were analyzed by SPSS (version 16) using appropriate statistical tests. P-values less than 0.05 were considered statistically significant. Results: Pain in the low back (27.9%) and neck (25%) was the most common complaint among the subjects. Overall, 80 tutors (70.79%) had symptoms of pain in at least one part of the body in the past year. The highest rate of complaints was related to laboratory tutors (94.73%). There was a statistically significant association between prevalence of MSDs and teaching time. Conclusions: The prevalence of MSDs among faculty members of Shahid Sadoughi University of Medical Sciences is high and more than the general population. The musculoskeletal complaints are significantly associated with teaching time.